Ingenious floral structure drives explosive pollination in Hydrilla verticillata (Hydrocharitaceae). (8th January 2020) - Zhang, Q.; Fu, W.‐L.; Wang, X.‐F.; Huang, L.‐J.
Abstract: In explosive pollination, many structures and mechanisms have evolved to achieve high‐speed stamen movement. The male flower of the submerged plant Hydrilla verticillata is reported to be able to release pollen explosively some time after leaving the mother plant time, but the mechanism of stamen movement and the related functional structure in this species are unclear. In this study, we observed the male flower structure and pollen dispersal process of H. verticillata . We analysed the stamen movements during the pollen dispersal process and conducted several controlled experiments to study the process of storage and release of elastic potential energy in explosive pollination. When the male flower of H. verticillata is bound to the united bracts, the sepals accumulate elastic potential energy through the expansion of basal extensor cells. After the male flower is liberated from the mother plant, the stamens unfold rapidly with the sepals under adhesion and transfer the elastic potential energy to the filament in seconds. Once stamens unfold to a critical angle, at which the elasticity of the filament just exceeds the adhesion between sepals and anthers, the stamens automatically rebound and release pollen in milliseconds. These results reveal that Catapult‐like stamens, spoon‐shaped sepals and enclosed united bracts in the spathe together constitute the functional structure in rapid stamen movement of H. verticillata . They ensure that the pollen can be released on the water surface, and thus adapt successfully to the pollen‐epihydrophilous pollination. Abstract : During flowering of Hydrilla verticillata, enclosed united bracts and spoon‐shaped sepals in the male spathe drive catapult‐like stamens to move rapidly by storing elasticity, transferring and releasing elastic potential energy to release pollen automatically and explosively after the male flower leaves the mother plant and reaches the water surface, which adapt successfully to the pollen‐epihydrophilous pollination.